Be Careful what you Ask for - Fluehr-Lobban, Carolyn (Hawwa, 2016)
The current Islamist government, ushered in by a military coup in 1989, declared that the Sudan must be governed by Islamic law or shari’a in accordance with what it called the Civilization Project. As expected, the personal status for Muslims laws, Ahwal Shakhsiyya, continued to be governed by shari’a as it has always been. However, the Sudanese society experienced unprecedented changes that are considered un-Islamic, and may be even punishable by law. In this paper two of those changes happened in the institution of marriage. This paper discusses two types of marriage, ‘Urfi and Misyar that are not part of the law, and traditionally unacceptable, and by law deemed by some to be illegal. Some scholars are seeking to normalize and may be legalize both types.